Influence of Error Factors on Transmission Contact for Spiral Bevel Gears - Wang Mingyang; Li Shuwen; Sun Yuehai (Jixie chuandong)
The full tooth flank contact characteristic of the line contact spiral bevel gear transmission is sensitive to errors. To obtain the influence of error factors on transmission contact for line contact spiral bevel gears, the contact simulation analysis with error factors is carried out. Firstly, based on the cutter head approximation machining method, a tooth flank mathematical model of the line contact spiral bevel gear is developed, and the correctness of this model is verified. Then, based on this model, the influence of installation errors and pitch deviation for line contact spiral bevel gears with different accuracy levels are analyzed, and the change law of the contact stress and deformation for the mating flank are obtained. The results show that, due to error factors, the line contact spiral bevel gear transmission will produce edge contact, which is mainly shown at the top, and then at the toe, not obvious at the root and the heel. Among the various errors analyzed, the pitch deviation and the pinion axis error have the great influence on the contact stress and deformation of the tooth flank, followed by the shaft spacing error and the shaft angle error, and finally the gear axis error. The research results can provide reference for the error control and modification design of the line contact spiral bevel gear.